Muslim-Christian polemics across the Mediterranean: the splendid replies of Shihab al-Din al-Qarafi (d. 684/1285) - Sarrió Cucarella, Diego R. (History of Christian-Muslim relations 1570-7350, 2015)
2.2 Muslim Disputes about the Qur ān3 The Abrogation and Falsification of the Torah; 3.1 Can God Change His Mind?; 3.2 The Falsification of the Torah; 4 Miscellanea; 4.1 The Ḥadīth of the Pen and Paper; 4.2 The Physical Pleasures of Paradise; 4.3 Fighting for God's Cause: Virtue or Vice?; 5 Concluding Remarks; Chapter 5 Christianity and the Innovation of A Wretched God; 1 The Christian Creed: Viler than Treachery; 2 Christian Innovated Practice and Behavior; 2.1 Christians and Circumcision; 2.2 Consumption of Pork; 2.3 The Offering of Bread and Wine.